The motor development of orphaned children with and without HIV: Pilot exploration of foster care and residential placement - Ferguson Gillian; Davids Nailah; Jelsma Jennifer (BMC, 2011)
Abstract Background The AIDS epidemic has lead to an increase in orphaned children who need residential care. It is known that HIV leads to delayed motor development. However, the impact of place of residence on motor function has not been investigated in the South African context. The aim of the study was therefore to establish if children in institutionalised settings performed better or worse in terms of gross motor function than their counterparts in foster care. A secondary objective was to compare the performance of children with HIV in these two settings with those of children who were HIV negative. Methods Forty-four children both with and without HIV, were recruited from institutions and foster care families in Cape Town. The Peabody Development Motor Scale (PDMS II) was used to calculate the total motor quotient (TMQ) at baseline and six months later. Comparisons of TMQ were made between residential settings and between children with and without HIV. Results Twenty-one children were infected with HIV and were significantly delayed compared to their healthy counterparts. Antiretroviral therapy was well managed among the group but did not appear to result in restoration of TMQ to normal over the study period. HIV status and place of residence emerged as a predictor of TMQ with children in residential care performing better than their counterparts in foster care. All children showed improvement over the six months of study. Conclusions Foster parents were well supported administratively in the community by social welfare services but their children might have lacked stimulation in comparison to those in institutional settings. This could have been due to a lack of resources and knowledge regarding child development. The assumption that foster homes provide a better alternative to institutions may not be correct in a resource poor community and needs to be examined further.